The Effects of Reflective Learning Integrated Process Writing Instructions on High School Students' Paragraph Writing Performance and Perception - Wirtu, Gebisa; Disasa, Rufael; Daba, Ebissa (International Journal of Language Teaching and Education, 2025)
This study examines the effects of reflective learning integrated process writing instructions on high school students' paragraph writing performance and perception. It also examines the correlation between students' paragraph writing performance and perception. A quasi-experimental research design and mixed method approach were employed, and a purposeful convenience sampling technique was used. Leka Nekemte High School, Nekemte town, West Oromia, Ethiopia, and grade eleven students were the participants in the study. Two intact sections were chosen as the experimental group (n = 30) and the other as the control group (n 30). The data were collected through tests, questionnaires, and semi-structured interviews. The study's findings revealed that the experimental group, which practiced paragraph writing through reflective learning, integrated process writing instructions, outperformed the control group, which conventionally practiced paragraph writing. Additionally, it indicates the experimental group developed a higher positive perception than the control group. These findings highlight the need for reflective learning integrated process writing instructions to improve high school students' paragraph writing performance and develop a positive perception of paragraph writing.